Association between objectively measured physical activity and body mass index with low back pain: a large-scale cross-sectional study of Japanese men - Hashimoto, Yuko (BMC Public Health, 2018)
BACKGROUND: The relationship between the combination of physical activity (PA) and body mass index (BMI) with low back pain (LBP) is unclear. The present study offers a cross-sectional assessment of how combinations of PA and BMI are related to LBP in Japanese men. METHODS: Participants were 4022 Japanese men (mean age = 47) who underwent regular clinical examinations. PA was measured using a uniaxial accelerometer and divided into tertiles (PA(high), PA(middle), PA(low)). A self-administered questionnaire was used to report on persistent LBP experience, drinking and smoking habits, and any existing lifestyle diseases. After covariance adjustment, a logistic regression model was used to assess how combinations of PA and BMI are related to persistent LBP. RESULTS: 428 of the participants had persistent LBP. A clear negative dose-response relationship was found between PA levels and persistent LBP (P for linearity = 0.012). Regarding BMI, odd ratios were shown to be higher in the overweight/obese category (BMI ≥ 25 kg/m(2)) than for the normal weight category (BMI < 25 kg/m(2)). When the PA(high) was taken as the reference in the normal weight category, odds ratios for PA(low) and PA(middle) in the normal weight category were shown to be high. Moreover, in the overweight/obese category, odd ratios for every fitness level were also high as for the normal weight category. CONCLUSION: The present study showed that both PA and BMI are related to persistent LBP. Also, the prevalence of persistent LBP became higher when PA(low) and high BMI are combined rather than the group of PA(high) and low BMI combination. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12889-018-5253-8) contains supplementary material, which is available to authorized users.